Kajian Elemen Fisik Kota Palembang berdasarkan Analisis Persepsi dan Unsur Elemen Pembentuk - Muhammad Fahri; Bangun I R Harsritanto; Helfa Rahmadyani (Universitas Negeri Gorontalo, 2023)
An image that arises based on people's memory is influenced by the history and culture of the people in a city. Palembang is one of the historical cities in Indonesia with the oldest trading system in Indonesia since ancient times known as the Venice city of the east. The formation of the image of a city is influenced by the physical elements of urban space. However, the development of the physical elements of Palembang City has never been known. Based on that, this study aims to determine the physical elements of Palembang City through physical objects in Palembang City. The scope of discussion of this study is in the form of determining the physical elements of Palembang City through Kevin Lynch's theory and public perception. The study will be conducted using a descriptive method with an exploratory Grounded Theory qualitative approach. The sampling technique uses non-probability sampling techniques and data collection of physical objects through sociological survey methods. The study found that the most influential constituent elements are preceded by nodes, landmarks, districts, paths and edges. The forming element of Palembang City is a physical object that is high in size and can be seen by the public from all corners of the city and is the center of community activity. The elements forming this city can be a consideration in determining the image of Palembang City.